2022
DOI: 10.1038/s41598-022-11408-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanisms of ABA-induced salinity tolerance in leaves and roots of rice

Abstract: Abscisic acid (ABA) plays a crucial role in response to abiotic stress as important small molecules in regulating metabolism. This study aimed to evaluate the ability of foliar spraying ABA to regulate growth quality at rice seedling stage under salt stress. Results demonstrated that salt stress strongly reduced all the growth parameters of two rice seedlings (‘Chaoyouqianhao’ and ‘Huanghuazhan’), caused prominent decrease in the levels of photosynthetic pigments (mainly in Huanghuazhan), photosynthesis and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 99 publications
4
29
0
Order By: Relevance
“…Under abiotic stress, genes related to the ABA signaling pathway AAO and ABA2 were induced to express and promote the rapid accumulation of ABA in plants [ 46 ]. ABA has been reported to regulate the expression levels of stress-tolerance-related genes, including APX , POD , LEA , and CAT , in several plant species [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under abiotic stress, genes related to the ABA signaling pathway AAO and ABA2 were induced to express and promote the rapid accumulation of ABA in plants [ 46 ]. ABA has been reported to regulate the expression levels of stress-tolerance-related genes, including APX , POD , LEA , and CAT , in several plant species [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MDA can be used to evaluate the extent of membrane lipid peroxidation and the antioxidant capacity of tissues and cells ( Chen et al., 2022 ; Li et al., 2022 ). In the present study, the MDA content in the leaves and roots of sugarcane seedlings showed an upward trend with increasing extract concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, under NaCl stress, applying exogenous abscisic acid in rice reduced the Na + content in the leaves and roots, and increased the K + , Mg 2+ and Ca 2+ content and antioxidant enzyme levels in the leaves and roots, thereby reducing the salt toxicity of seedlings. It showed that ABA is beneficial for protective membrane lipid peroxidation and enhances salt tolerance by regulating antioxidant defense systems and endogenous hormone balance [ 59 ]. ABA enhances tolerance to alkaline stress by initiating antioxidant defense system in roots of rice seedlings and upregulating tolerance-related genes [ 60 ].…”
Section: Discussionmentioning
confidence: 99%